2014
DOI: 10.7554/elife.01440
|View full text |Cite
|
Sign up to set email alerts
|

Dual mode of embryonic development is highlighted by expression and function of Nasonia pair-rule genes

Abstract: Embryonic anterior–posterior patterning is well understood in Drosophila, which uses ‘long germ’ embryogenesis, in which all segments are patterned before cellularization. In contrast, most insects use ‘short germ’ embryogenesis, wherein only head and thorax are patterned in a syncytial environment while the remainder of the embryo is generated after cellularization. We use the wasp Nasonia (Nv) to address how the transition from short to long germ embryogenesis occurred. Maternal and gap gene expression in Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 85 publications
5
91
0
Order By: Relevance
“…In contrast to this long-germ mode of segmentation, most insects and other arthropods exhibit a short-germ mode of segmentation, during which only a few anterior segments are generated simultaneously and subsequently a speciesspecific number of posterior segments are added sequentially from a posterior growth zone or segment addition zone (SAZ) (Davis and Patel, 2002;Tautz, 2004;Peel et al, 2005;McGregor et al, 2009). Note, however, that these modes of segmentation may not always be discrete because a mixed mode of segmentation has recently been proposed for Nasonia vitripennis (Rosenberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this long-germ mode of segmentation, most insects and other arthropods exhibit a short-germ mode of segmentation, during which only a few anterior segments are generated simultaneously and subsequently a speciesspecific number of posterior segments are added sequentially from a posterior growth zone or segment addition zone (SAZ) (Davis and Patel, 2002;Tautz, 2004;Peel et al, 2005;McGregor et al, 2009). Note, however, that these modes of segmentation may not always be discrete because a mixed mode of segmentation has recently been proposed for Nasonia vitripennis (Rosenberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade or so, several important genetic, genomic, and cell biological studies have been conducted in the jewel wasp N. vitripennis 19,[32][33][34][35] . These studies have been facilitated by the development of several important sgRNA #Injected (31) 62 (17) 659 (100) 271 (100) C 12 (7) 0 (0) 93 (35) 57 (22) 1318 (100) Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of pair-rule gene expression and function was performed in Nasonia; the results suggested that, in fact, the species exhibits dual modes of embryogenesis, a Drosophila-like mode at the anterior region and a Tribolium-like mode at the posterior region. Knockdown of Nasonia pair-rule genes, Nveve, odd and h (a hairy homolog), results in a loss of alternate anterior segments and a loss of posterior segments, and also Nvodd is expressed in waves (Rosenberg et al, 2014).…”
Section: Evolution and A Model Of Bombyx Segmentation Mechanismsmentioning
confidence: 99%